Anti-inflammatory panacea? The expanding therapeutics of interleukin-1 blockade. Issue 3 (May 2016) - Kahlenberg, J. Michelle
Abstract : Purpose of review: Blockade of interleukin (IL)-1 signaling is one of the oldest biologic therapies, yet the use of these agents is on the rise as the role of IL-1 activation is being recognized in a wide spectrum of inflammatory disorders. This review will cover established and emerging uses of IL-1 antagonism in rheumatic diseases. Recent findings: Expanding off-label indications for IL-1 blockade include neutrophil-dominant skin diseases, including pyoderma gangrenosum, hidradenitis supperativa, and pustular psoriasis. There is also increasing evidence for the use of IL-1 blockade in heart failure associated with rheumatic diseases. Somatic mosaicism in NLRP3 may explain the onset of later-in-life presentations of periodic fevers which are responsive to IL-1 blockade. Of importance, clinical response to anti-IL-1 therapy does not always denote protection from autoinflammatory disease complications such as macrophage activation syndrome or amyloidosis. Summary: Indications for IL-1 blocking therapies will likely continue to broaden, but given the rarity of many rheumatic diseases which respond to such treatment, rigorous, large clinical trials for each indication are unlikely to occur. Thus, recommended use of these medications will often fall to the discretion of the astute physician. However, medication cost and hurdles of insurance approval, rather than drug efficacy, may be the primary limitation for more widespread use.